Android-Based RCSM Application for Implementation of Preventive Maintenance on CNC Production Machine - Fauzi, Mohammad; Erdani, Yuliadi; Sambas, Achmad (Politeknik Ganesha Medan, 2023)
Preventive maintenance (PM) implementation at POLMAN Bandung is scheduled to follow the lecture schedule so that the implementation of activities does not interfere with the lecture process. Even though the scheduling of preventive maintenance activities at POLMAN Bandung has been made quite well, there are problems in its implementation, including some activities that were not detected in the previous PM implementation, both in the form of activity reports and machine history updates. This can confuse subsequent pm implementers, as it can result in mishandling. As for the cause of the problem, there are two possibilities, namely the implementation of preventive maintenance is not carried out or the implementation of preventive maintenance has been carried out, but reports on the implementation of activities are not prepared and stored by procedures (human error). To overcome this, the researchers developed an Android-based application that functions as a reminder, recorder, and controller, for the pm process, named Reminder & Control System Management (RCSM). RCSM will remind, the implementers, to be on schedule, carry out a remind mechanisms, and information broadcast and validation until the completion of preventive maintenance activities is acceptable to the relevant authorities. Likewise, for reporting and recording engine history a system will be created with a similar mechanism. The results that have been achieved are the application software prototype reaching 100% and several field trials have been carried out. This application can direct pm implementers to avoid misuse of pm implementation procedures so that preventive maintenance implementation data can be recapitulated.